2021
DOI: 10.3390/s21072539
|View full text |Cite
|
Sign up to set email alerts
|

Smart Wearables for Cardiac Monitoring—Real-World Use beyond Atrial Fibrillation

Abstract: The possibilities and implementation of wearable cardiac monitoring beyond atrial fibrillation are increasing continuously. This review focuses on the real-world use and evolution of these devices for other arrhythmias, cardiovascular diseases and some of their risk factors beyond atrial fibrillation. The management of nonatrial fibrillation arrhythmias represents a broad field of wearable technologies in cardiology using Holter, event recorder, electrocardiogram (ECG) patches, wristbands and textiles. Impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 146 publications
0
44
0
Order By: Relevance
“…Step count monitoring is popular in the general population, using wearable devices such as smartphones, smartwatches, or wearable pedometers [ 43 ]. Just as described above for the resting heart rate, population-based cohort studies showed that a higher number of steps per day correlated with a lower mortality rate in a cohort of adults [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Step count monitoring is popular in the general population, using wearable devices such as smartphones, smartwatches, or wearable pedometers [ 43 ]. Just as described above for the resting heart rate, population-based cohort studies showed that a higher number of steps per day correlated with a lower mortality rate in a cohort of adults [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that only 20% of patients think there are more advantages than disadvantages in the application of AI, and 35% of participants would refuse to implement their disease-related intervention through AI [107]. Patients worry about losing connection with clinicians and are also concerned about the misuse of AI that can cause additional damage to their health, which may be caused by inadequate follow-up and insufficient education [108]. Achieving public trust is necessary to operate AI-based cardiac telerehabilitation [109].…”
Section: Trustworthiness and Willingness To Use Aspectsmentioning
confidence: 99%
“…Nowadays, wearable devices—such as wrist bands and smartwatches—have biological sensors; thus, their complexity has not only the potential to track health, wellness, and fitness but also the potential to diagnose cardiovascular diseases. This can be prescribed by a health care provider and influence therapeutic decisions [ 91 ].…”
Section: Wearable Sensors In Health Monitoringmentioning
confidence: 99%